2013
DOI: 10.5194/acp-13-4783-2013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between summertime and wintertime Arctic Ocean primary marine aerosol properties

Abstract: Primary marine aerosols (PMAs) are an important source of cloud condensation nuclei, and one of the key elements of the remote marine radiative budget. Changes occurring in the rapidly warming Arctic, most importantly the decreasing sea ice extent, will alter PMA production and hence the Arctic climate through a set of feedback processes. In light of this, laboratory experiments with Arctic Ocean water during both Arctic winter and summer were conducted and focused on PMA emissions as a function of seas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The predicament of multiply charged particles may well have been an issue in previous laboratory plunging jet sea spray experiments, when either an impactor was not used (or not stated) or the particle sizer had an upper cutoff significantly lower than the cutoff of the impactor used [e.g., Sellegri et al, 2006;Hultin et al, 2010Hultin et al, , 2011Zábori et al, 2012bZábori et al, , 2012aZábori et al, , 2013. We expect such problems to be largest when particle generation is induced by a plunging jet because aerosol production by forcing air through a frit below the water surface typically results in a smaller proportion of large particles than aerosol production by a plunging jet.…”
Section: Particle Size Distributionsmentioning
confidence: 99%
“…The predicament of multiply charged particles may well have been an issue in previous laboratory plunging jet sea spray experiments, when either an impactor was not used (or not stated) or the particle sizer had an upper cutoff significantly lower than the cutoff of the impactor used [e.g., Sellegri et al, 2006;Hultin et al, 2010Hultin et al, , 2011Zábori et al, 2012bZábori et al, , 2012aZábori et al, , 2013. We expect such problems to be largest when particle generation is induced by a plunging jet because aerosol production by forcing air through a frit below the water surface typically results in a smaller proportion of large particles than aerosol production by a plunging jet.…”
Section: Particle Size Distributionsmentioning
confidence: 99%
“…A series of laboratory systems designed to replicate sea spray aerosol production by whitecaps have shown that the number production flux increases markedly as water temperatures are decreased (e.g. Salter et al, 2014;Zábori et al, 2013;Bowyer et al, 1990). In contrast, observational data from the field, such as chemical analysis of particulate matter smaller than 10 µmin diameter (PM 10 ) or total suspended mass, have often been used to infer that sea spray aerosol production increases with higher sea surface temperatures due to higher observed concentrations at lower latitudes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1a) in a marine laboratory during late Arctic winter conditions (from the 15 February to the 7 March 2010) and during late Arctic summer conditions (from the 24 August to the 7 September 2009). This paper presents results of the winter measurements, whereas Zábori et al (2012) will compare summer and winter conditions. Sea water samples each of 180 l were collected at three different locations in the vicinity of Ny-Ålesund to cover possible differences between outer-fjord and inner-fjord conditions, including the potential influence of the Kongsbreen glacier (Fig.…”
Section: Experimental Sitementioning
confidence: 99%